Manajemen Pengembangan Kompetensi Pedagogik Guru dalam Upaya Meningkatkan Mutu Proses Pembelajaran PAI - Sodikin, Hasan; Sukandar, Ahmad; Setiawan, Marwan (CV. Media Publikasi Profesional, 2022)
This research is motivated by a phenomenon that shows a decline in quality in the world of education today. Many teachers lack mastery of pedagogic competence, professional competence, personality competence and social competence which are the basis of the learning process. The low quality of educators makes it difficult to achieve the desired learning objectives. To face these challenges, teachers must continuously learn in an effort to develop their competencies. Islam Tarbiyatul Falah and SMP PGRI Telukjambe?. (2) How is the Professional Competence of Teachers in Improving the Quality of Learning in Tarbiyatul Falah Islamic Middle School and PGRI Telukjambe Junior High School? (3) How is the Teacher's Personality Competence in Improving the Quality of Learning in Tarbiyatul Falah Islamic Middle School and PGRI Telukjambe Middle School? (4) How is Social Competence? Teachers in Improving the Quality of Learning in Tarbiyatul Falah Islamic Middle School and PGRI Telukjambe Middle School? This research was conducted in two research locations, namely Islamic Middle School Tarbiyatul Falah and SMP PGRI Telukjambe using descriptive qualitative analytical method. The theoretical orientation used is based on a phenomenological study approach using a multi-site study. Data and data sources: (1). Primary: principals, teachers, staff and students. (2). Secondary: documentation, and archives. This research data collection was carried out by participant observation, in-depth interviews and documentation techniques. Checking the data again by triangulation, data disclosure procedures regarding teacher competence in improving the quality of learning. For data analysis, researchers collected data then data reduction, data presentation and then drew conclusions. From the results of this study, the researchers showed that: (1) The pedagogical competence of teachers in improving the quality of learning in Tarbiyatul Falah Islamic Middle School and PGRI Telukjambe Middle School includes competence in terms of preparing learning tools, developing curriculum, improving human resources through workshops, using models and methods, media as well as the selection of teaching materials in accordance with the needs and development of students. (2) The professional competence of teachers in improving the quality of learning at Islamic Middle School Tarbiyatul Falah and SMP PGRI Telukjambe includes competence in terms of mastery of material, organization of material, delivery of material and management of learning. (3) The competence of the teacher's personality in improving the quality of learning at Islamic Middle School Tarbiyatul Falah and SMP PGRI Telukjambe includes competence in terms of providing good role models, discipline and teacher responsibility in carrying out their duties. (4) The social competence of teachers is shown by the communication between teachers and students through teaching and learning activities.